Pleknaamsverandering in Suid- Afrika: bevestiging van ANC mag, gesag, wettigheid en ‘selfrespek’ - Moll, Johan (Acta Academica: Critical views on society, culture and politics, 2007)
Power and authority appear to underlie changes in nomenclature resulting from a need to assure and convince the supporters of a new rregime that names which previously symbolised their oppression and domination have become unacceptable and must be replaced by names suiting the ethos of the new, liberating dispensation. New symbols are generated to ensure the acceptability of the new regime and to reflect the new collective values and history which will be prioritised and considered to be of importance. The symbolism underlying changes in nomenclature and the ANC’s realisation of the significance of renaming form the main focus of this article, which is based mainly on newspaper sources. Throughout South Africa the tangible symbolism of the success story of liberation may be identified: in street names commemorating the “terrorists” of the previous era, in the decolonisation of the names of provinces, and in other indisputable testimony that — by means of changes in nomenclature, inter alia — this country has also finally become inherently part of Africa.